2015
DOI: 10.15640/jehd.v4n2a15
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Voices Inside Schools: Issues of Sexuality in Upper Classes in Primary Schools in Botswana

Abstract: The absence and or presence of sexuality education in our curriculum have provoked several debates within the Botswana society. Some people feel that issues of sexuality should be incorporated in our school curriculum while others believe that they should not. Therefore, the purpose of this study was to explore the teachers' and students' perceptions on issues of sexuality in primary schools in Botswana. The study focused on teachers and students in selected primary schools in Northern and Central regions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Studies in Botswana, Nigeria and South Africa have shown that sexuality education may contribute to overcoming the adolescents SRH challenges that Zambia and other countries face [1517]. At the core of the Zambian sexuality education policy is the idea that there is a substantial need to support adolescents in delaying their sexual debut, to reduce the number of sexual partners and to increase safer sexual practices [1517].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in Botswana, Nigeria and South Africa have shown that sexuality education may contribute to overcoming the adolescents SRH challenges that Zambia and other countries face [1517]. At the core of the Zambian sexuality education policy is the idea that there is a substantial need to support adolescents in delaying their sexual debut, to reduce the number of sexual partners and to increase safer sexual practices [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Botswana, Nigeria and South Africa have shown that sexuality education may contribute to overcoming the adolescents SRH challenges that Zambia and other countries face [1517]. At the core of the Zambian sexuality education policy is the idea that there is a substantial need to support adolescents in delaying their sexual debut, to reduce the number of sexual partners and to increase safer sexual practices [1517]. Backed by evidence on its positive effects on adolescents’ level of knowledge, skills, attitudes and values related to sex and sexuality, CSE has been promoted in a series of global policy guidelines and recommended to be integrated into ordinary school curricula [3, 1517].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ethiopia, Ghana, Kenya, Peru and Guatemala, teachers and students of the same gender had a positive effect [15]. Studies conducted in Southern and West Africa (namely, Botswana, Zimbabwe, and Nigeria) concluded that teachers with negative attitudes and perceptions regarding CSE hindered progress [33,36,48]. Similarly, the reaction of community and religious leaders and parents had a significant impact on the acceptance of CSE.…”
Section: Discussionmentioning
confidence: 98%